DEA to bare and water-solvated pyrimidine clusters. (August 2015) - Neustetter, Michael; Aysina, Julia; da Silva, Filipe Ferreira; Denifl, Stephan
Synopsis: In the present work we investigate the interaction of low energetic electrons with biologically relevant molecules. Our aim is to observe differences in the fragmentation pattern in the case of isolated molecules, bare clusters and water-solvated clusters. In this context we present the first results regarding electron attachment to nano-solvated biomolecule clusters.